Patterns of guanaco distribution and microhabitat use in Tierra del Fuego: From protected to sheep ranching areas - Iranzo, Esperanza C.; Smith, Carollyne; Moraga, Claudio A.; Radic Schilling, Sergio Javier; Corti, Paulo (My University, 2022)
Wild herbivore distribution responds to habitat and forage availability modulated by predation risk and inter-specific interactions. Nowadays, the study of distribution and abundance of wild and domestic herbivores have regained importance to understand and diminish conservation conflicts in productive lands worldwide. Contiguous ranching and protected areas have created conflicting scenarios when wild ungulate populations increase and redistribute in livestock rangelands, because of competition for food and disease transmission. Consequently, understanding wild ungulate distribution and density patterns is critical to inform efficient management strategies for livestock grazing and wild ungulate coexistence. Here we analyze guanaco (Lama guanicoe) density and distribution, and compare habitat and microhabitat use (plant biomass, species richness, and diversity) in a protected area and in surrounding sheep ranches of Tierra del Fuego. Density of guanaco was similar between protected area and ranches, but proportion of groups and average group size were larger on ranches, and total guanaco density was also higher outside than within the protected area, which contrasts with previous studies. Use of microhabitat features was also different between both management regimes. Guanaco used areas with higher vegetation biomass, plant composition and richness in the protected area than on ranches. These results suggest that both intrinsic (socio-biological) and extrinsic (forage availability and human distur-bance) factors influence density and distribution patterns as well as microhabitat use by the guanaco, which have large implications for its conservation.
Keywords: guanaco density; herbivore distribution; sheep ranching; wild herbivore; lama guanicoe